Duty of Candour legislation in post-colonoscopy colorectal cancer: a prospective cohort study - Saunsbury, Emma; Burr, Nicholas E.; Beaton, David; McSweeney, Kate; Mason-Higgins, Jo; Trudgill, Nigel; Morris, Eva J. A.; Valori, Roland (Endoscopy, 2024)
This study investigated the application of Duty of Candour (DoC) legislation in the context of post-colonoscopy colorectal cancers (PCCRCs). DoC mandates transparent disclosure of notifiable safety incidents to patients in the English National Health Service, including incidences leading to severe or moderate harm. This study aimed to analyze the application of DoC in PCCRCs, improve understanding of the legislation, and identify challenges in DoC implementation.A national audit of PCCRCs was conducted between September 2021 and May 2022. PCCRCs were identified using linked administrative datasets, and root-cause analyses were performed using structured templates. “Avoidability” and harm were categorized into specific levels, and guidance was provided on improving consistency in judgments.16% of 1724 PCCRCs resulted in major harm or death, of which 27% (75) were probably or definitely avoidable. Hospitals deemed DoC discharge necessary in only 53% of these cases. When including moderate harm, 11% of all PCCRCs would trigger DoC discharge, yet this was deemed necessary in only 45% of such cases.There is inconsistent application of DoC in PCCRC cases. Challenges include determining “avoidability” and harm, particularly when diagnosis is delayed. Clearer guidance and definitions of harm are needed to improve adherence to regulations.